Passivity-Based Safe Maneuvering Control of Mechanical Systems With Input Constraints - Mingyue Cui; Yanzhuang Wei (IEEE Access)
For mechanical systems with input constraints, safe maneuvering control is investigated in this paper. How to accomplish the maneuvering task without violating safety constraints is the main challenge. To address the input constraints, the input constraints are expressed as state constraints of the augmented system by introducing a dynamic controller. First, a passivity-based desired controller is designed to fulfill the required maneuvering task without considering the multiple safety constraints. Then, multiple safety constraint functions are combined into a differentiable safety constraint function. Moreover, by using quadratic programming, a synthesis method for the safety controller with minimum deviation from the desired controller is given. Finally, the effectiveness of the proposed control strategy is demonstrated using a three-wheeled omnidirectional mobile robot.